Pengaruh Harga Dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan Pada Outlet Baso Aci Acila Di Gulun Kota Madiun - Gabriel Jesmeison Purba; Ninik Srijani; Wikanso Wikanso (CV. ITTC INDONESIA, 2023)
This study aims to: (1) determine the effect of price on customer satisfaction in baso aci acila, (2) determine the effect of service quality on customer satisfaction in baso aci acila, (3) determine price and service quality on customer satisfaction in baso aci acila. This research method uses quantitative research with SPSS version 26 as a data processing tool. The data collection technique uses a questionnaire and documentation. Isindetal sampling is used as a technique for sampling. The population in this study are baso aci acila customers. The sample in this study were 96 respondents. The results of this study indicate that the price variable test (X1) on customer satisfaction variable (Y) partially indicates a significant positive reaction. The results obtained are based on the results of the t test with a value of 0.000 <0.05 which indicates a positive result and H1 is acceptable. The partial test of service quality variable (X2) on customer satisfaction variable (Y) also shows a significant positive reaction. The results obtained are based on the results of the t test with a value of 0.000 <0.05 which indicates a positive result and H2 is acceptable. the results of the f test simultaneously show that the price variable (X1) and service quality (X2) have a significant positive effect on customer satisfaction (Y) with fcount > ftable 3.092 simultaneously showing positive results and H3 is acceptable. This explains that the variable price (X1) and service quality (X2) can simultaneously affect customer satisfaction at baso aci aila in Gulun, Madiun City.